2010
DOI: 10.1111/j.1469-8137.2010.03382.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting trait responses in plant communities to experimental and geographic variation in precipitation

Abstract: Summary Patterns of precipitation are likely to change significantly in the coming century, with important but poorly understood consequences for plant communities. Experimental and correlative studies may provide insight into expected changes, but little research has addressed the degree of concordance between these approaches. We synthesized results from four experimental water addition studies with a correlative analysis of community changes across a large natural precipitation gradient in the United State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
149
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(166 citation statements)
references
References 57 publications
14
149
3
Order By: Relevance
“…Variation among species in mean specific leaf area (SLA; leaf area/dry mass; or its inverse, termed leaf mass per unit area) has been found to correlate well with among-species variation in key physiological attributes such as leaf longevity (LL), water use efficiency (WUE), and relative growth rate (RGR). Species with high SLA and RGR, and low LL and WUE, are more prevalent in wetter climates (34) and in wetter years (35) and tend to increase disproportionately in response to experimental watering (36) and natural precipitation increase (37). Several previous studies have found that high-SLA species are especially vulnerable to decline or loss under aridification (38,39).…”
mentioning
confidence: 99%
“…Variation among species in mean specific leaf area (SLA; leaf area/dry mass; or its inverse, termed leaf mass per unit area) has been found to correlate well with among-species variation in key physiological attributes such as leaf longevity (LL), water use efficiency (WUE), and relative growth rate (RGR). Species with high SLA and RGR, and low LL and WUE, are more prevalent in wetter climates (34) and in wetter years (35) and tend to increase disproportionately in response to experimental watering (36) and natural precipitation increase (37). Several previous studies have found that high-SLA species are especially vulnerable to decline or loss under aridification (38,39).…”
mentioning
confidence: 99%
“…The importance of intraspecific variation in determining trait-environmental relationships and trait-based community assembly is becoming increasingly recognized (Ashton et al 2010;Jung et al 2010;Sandel et al 2010). We examined trait plasticity in G. cuneata, which occurred across all sites examined here and was also the most abundant species at most sites (Andersen et al 2010a).…”
Section: Linking Functional Traits and Species Distribution Patternsmentioning
confidence: 99%
“…Habitat filtering can lead to changes in trait composition along environmental gradients as a result of either turnover in species composition or differences in species abundance (Keddy 1992;Cornwell and Ackerly 2009;Sandel et al 2010) or intraspecific variation due to plasticity or genetic variation (Cornwell and Ackerly 2009;Hulshof and Swenson 2010;Jung et al 2010). Whereas most trait-based studies focus on species mean trait values, recent work has incorporated intraspecific variation to trait-based frameworks, adding a greater power to detect trait-environment linkages (Cornwell and Ackerly 2009;Hulshof and Swenson 2010;Jung et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations